Microbial landscape of the oral cavity in chronic recurrent aphthous stomatitis - Pulatova R.S. (Zien Journals, 2022)
The article describes studies of the microflora of the oral mucosa, studied the quantitative ratios of normal representatives of each biotope, as well as the presence and number of opportunistic and pathogenic microorganisms. Based on the results obtained, the author concluded that helminthic invasion worsens the degree and course of dysbiosis of the mouth and intestines, and also noted the relationship between the duration of the course of chronic recurrent aphthous stomatitis and dysbiosis of the oral cavity
Keywords: Oral mucosa; conditionally pathogenic microorganisms; pathogenic microorganisms